2021
DOI: 10.31234/osf.io/us4dc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nostalgia Causes a Preference for Regressive Social Change

Abstract: A broad literature demonstrates that nostalgia – a positive emotion associated with sentimental longing for the past – offers many psychological benefits for the individual. In contrast, we present seven studies showing that nostalgia, measured and manipulated, is associated with increased support for regressive social norms and policy. In the first four studies, we show that nostalgia is associated with opposition to smoke-free laws, preference for unsafe cars, expressions of benevolent sexism and opposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although most of the studies demonstrate that collective nostalgia is associated with conservative world views (Baldwin et al, 2021;Lammers, 2023;Smeekes et al, 2021), findings suggest that restorative collective nostalgia may also be related to liberal or leftwing political views (Bonnett, 2010) or to populist attitudes (Van Prooijen et al, 2022). To make the picture even more complex, Lammers and Baldwin (2018) demonstrated that conservatives are willing to accept liberal political ideas if those are presented with a past rather than future focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of the studies demonstrate that collective nostalgia is associated with conservative world views (Baldwin et al, 2021;Lammers, 2023;Smeekes et al, 2021), findings suggest that restorative collective nostalgia may also be related to liberal or leftwing political views (Bonnett, 2010) or to populist attitudes (Van Prooijen et al, 2022). To make the picture even more complex, Lammers and Baldwin (2018) demonstrated that conservatives are willing to accept liberal political ideas if those are presented with a past rather than future focus.…”
Section: Discussionmentioning
confidence: 99%
“…This plurality reveals the multidimensionality and complexity of nostalgia. Whereas in psychology nostalgia has been viewed predominantly as beneficial, in other social sciences, such as political science and sociology, nostalgia is often associated with negative social phenomena: backwardness, reactionism, and resistance to change (Baldwin et al, 2021;Bauman, 2017;Lammers, 2023; for a review, see Jacobsen, 2020aJacobsen, , 2022. In an attempt to reconcile these two approaches, a distinction was recently made in psychology between personal nostalgia-a psychological resource with mostly positive consequences-and collective nostalgia, which-although a source of group identity-leads to prejudice against foreign ethnic groups and reactionary ideologies (Sedikides & Wildschut, 2019;Smeekes et al, 2014;Smeekes et al, 2023).…”
Section: Nostalgia: From a Disease To A Curementioning
confidence: 99%